Simplify:
$(x^2-3x + 2) (5x- 2) - (3x^2 + 4x-5) (2x- 1)$

AcademicMathematicsNCERTClass 8

Given:

$(x^2-3x + 2) (5x- 2) - (3x^2 + 4x-5) (2x- 1)$

To do:

We have to simplify the given expression.

Solution:

$(x^2-3x + 2) (5x- 2) - (3x^2 + 4x-5) (2x- 1)=[5x (x^2 - 3x + 2) -2 (x^2 - 3x + 2)] - [2x (3x^2 + 4x - 5) -1 (3x^2 + 4x - 5)]$

$= [5x^3 - 15x^2 + 10x - 2x^2 + 6x - 4] - [6x^3 + 8x^2 - 10x - 3x^2 - 4x + 5]$

$= [5x^3 - 15x^2 - 2x^2 + 10x + 6x - 4] - [6x^3 + 8x^2 - 3x^2 - 10x - 4x + 5]$

$= (5x^3 - 17x^2 + 16x-4) - (6x^3 + 5x^2 - 14x + 5)$

$= 5x^3 - 17x^2 + 16x - 4 - 6x^3 - 5x^2 + 14x - 5$

$= 5x^3 - 6x^3 - 17x^2 - 5x^2 + 16x + 14x - 4 - 5$

$= -x^3 - 22x^2 + 30x - 9$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements